A Review on Formulation and Therapeutic Applications of Herbal Analgesic Creams: Review Article (Journal of Pharma Insights and Research, 2025)
Herbal analgesic creams serve as an effective alternative in pain management, using bioactive compounds from medicinal plants. The integration of traditional botanical knowledge with modern pharmaceutical techniques has led to the development of effective topical formulations. The main ingredients such as Calotropis gigantea, methyl salicylate, and essential oils contribute analgesic and anti-inflammatory properties, while excipients including liquid paraffin, beeswax, and cetyl alcohol provide optimal rheological characteristics. The formulation process involves systematic extraction of plant materials, preparation of cream base, and incorporation of active constituents under controlled conditions. These preparations demonstrate notable efficacy in alleviating various types of pain, including musculoskeletal disorders and inflammatory conditions. Standardized evaluation parameters such as pH, spreadability, viscosity, and stability studies ensure product quality and consistency. The therapeutic potential of these formulations is attributed to the synergistic effects of multiple bioactive compounds, offering advantages such as reduced systemic side effects and improved patient compliance. The development of herbal analgesic creams helps in the management of pain naturally and provides a viable alternative to conventional synthetic formulations